Association between maternal and neonatal factors and Apgar in usual risk neonates - Jéssica Pinto Saraiva; Sibylle Emilie Vogt; Jéssica da Silva Rocha; Elysângela Dittz Duarte; Delma Aurélia da Silva Simão (Universidade Federal do Ceará, 2018)
Objective: to verify the association between maternal and neonatal factors and the Apgar score <7 at five minutes of life. Methods: cross-sectional study with 134 newborns. For the analysis of the data collected through an instrument developed by the researchers, we used the description of the absolute and relative frequencies and applied the Chi-square or Fisher's exact tests. Results: of the total number of newborns, 63.0% had primigravida mother, 56.0% were male, 79.0% had been born from normal delivery, 65.0% had required oxygen and 45.0% had been resuscitated in the delivery room. Among women, 71.0% had made use of oxytocin. Conclusion: use of oxytocin, oxygen and resuscitation in the delivery room showed a significant association with Apgar <7 at five minutes of life. Birth weight, rupture membrane time, meconium clearance, type of delivery, and parity were not related to the low Apgar score.